METHOD FOR COLLECTING COELOMOCYTES FROM EURYTHOE COMPLANATA (ANNELIDA: AMPHINOIDAE) WITH POTENTIAL APPLICATION IN TOXICOLOGY - Arredondo, Luis (2020)
Benthic organisms have been proposed as good indicators of disturbance in marine environments, particularly because most toxins fall to the bottom of the sea affecting benthic communities. A non-invasive method for collecting coelomocytes was developed using the marine polychaete Eurythoe complanata with potential applications in xenobiotic toxicology. The extrusion method used produced the expulsion of 95% of the coelomic fluid, showing a greater efficiency than the puncture method in Lumbricus terrestris with regard to the total number of coelomocytes and cellular viability. The total coelomocyte count by this method was 6 -1 6 -12.6 x 10 cells·mL vs 1.4 x 10 cells·mL for the puncture method. The results indicate that coelomocyte numbers completely recover at 20 days after extrusion, using the total cell count, cell viability and differential count. This method was developed to study immunotoxicity of xenobiotics at the sediment-water interface of marine environments.